Editorial Note: A Long-term Endeavor of Citations in the Global South Open Access Journals - Sekarasih, Laras; Jaya, Edo S.; Shadiqi, Muhammad Abdan (Makara Human Behavior Studies in Asia, 2023)
Citations have become a “currency” of research quality. If the number of papers published is a parameter of scholars’ productivity, the number of citations received by each paper serves as an indicator of the quality of the research. The number of citations is often used to assess the quality of an article. In this bibliometric measure, papers that attract citations are considered to have a meaningful contribution. A high number of citations, especially when they come immediately after the papers are published, indicates that the paper is well accepted by scholars in the field and contributes to the advancement of science.